The The Analysis of Pros and Cons Regarding the Arrival of Rohingya Refugees: Religious, Humanitarian, and Socio-Economic Implication - Hapid Durohman; Fajar Andrian Sutisna; Muhamad Ridho (Journal of Islamic Civilization, 2023)
The Rohingya refugee crisis has garnered global attention, eliciting both pros and cons to the dispersion of Rohingya refugees across different nations. This research analyzes the pros and cons of the Rohingya refugee situation and its implications for religion, humanity, society, and the economy. The research method uses qualitative descriptive analysis included in the literature review, which takes secondary data from sources such as the Immigration Detention Center, UNHCR, and IOM. The research result show four main backgrounds to the Rohingya crisis: religious, humanitarian, social, and economic. The study identifies numerous hoaxes and hate speech targeting the Rohingya, causing societal polarization and the disruption of social harmony. The same of religion and human values becomes the primary reason to assist Rohingya refugees. However, societal rejection also occurs due to the presence of certain Rohingya individuals who violate local norms and religious principles. From a social and economic perspective, helping the Rohingya ethnic group is an effort to prevent human trafficking transactions. However, it has the potential to cause social jealousy. Rohingya refugees negatively impact the economy, but in Malaysia, they contribute positively to the informal sector. Resolving this crisis demands international cooperation, humanitarian aid, diplomatic efforts, and a commitment to human rights for concrete solutions.